Ionic‐Liquid‐Gel Surfaces Showing Easy‐Sliding and Ultradurable Features. Issue 10 (12th May 2015) - Ding, Yi; Zhang, Jiajing; Zhang, Xiqi; Zhou, Yahong; Wang, Shutao; Liu, Hongliang; Jiang, Lei
<x xml:space="preserve">Abstract</x> Programmable and durable: A strategy for the rational design of ultradurable ionic‐liquid‐gels (ILGs) for either water droplet or decane droplet mobility is developed. The tuning is accomplished via rational manipulations of compatibility of testing liquids with crosslinked polymer networks as well as ionic liquids trapped within it. Importantly, the designed ILGs can maintain their easy‐sliding property for quite a long term, and endure high temperatures.